2020
DOI: 10.1111/hsc.13219
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary validation of a brief household food insecurity screening tool for paediatric health services in Australia

Abstract: Children from food insecure households are more likely to have substandard food and nutritional intakes, and experience developmental delays, behaviour issues and increased use of health services. In Australia, screening for household food insecurity (HFI) within health services is not undertaken routinely, limiting opportunities to optimise nutrition and healthcare. This research aimed to (a) identify the prevalence, potential determinants and outcomes of HFI among paediatric outpatients in two Queensland hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Further research is required to quantify the extent of food insecurity amongst school students and to independently evaluate the food relief efforts of schools which require substantial resources. This would inform a more robust, coordinated and equitable policy response from government to address school food insecurity and help address the evidence‐gap which suggests research on food security interventions for children is lacking in robustness and the best options for the future are systems‐based approaches in both the implementation and evaluation of interventions 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is required to quantify the extent of food insecurity amongst school students and to independently evaluate the food relief efforts of schools which require substantial resources. This would inform a more robust, coordinated and equitable policy response from government to address school food insecurity and help address the evidence‐gap which suggests research on food security interventions for children is lacking in robustness and the best options for the future are systems‐based approaches in both the implementation and evaluation of interventions 9 …”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the FAO estimated 13.5% of households experienced food insecurity. 7 There is known higher prevalence of food insecurity among specific sub-groups in Australia including single-parents, 8 households with children with special healthcare needs 9 and families living in socioeconomically deprived neighbourhoods. 5 A range of food security strategies (i.e.…”
mentioning
confidence: 99%
“…Including routine screening and then providing programs that link food insecure households or individuals to the services via health care settings is a solution that has grown out of the suggestion that supporting food security can lead to improvements in population health [46,47]. There is increasing interest in routine screening and the role of healthcare systems in addressing food insecurity in non-pregnancy healthcare settings [48,49]. The International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) Z codes (Z55-Z65) allow for the classification and documentation of the social determinants of health in electronic medical health records.…”
Section: Institutional Level Solutionsmentioning
confidence: 99%
“…In Australia, there is work underway that seeks to highlight the link between health care settings and actions that address food insecurity. For example Kerz, Bell [48], have validated a brief tool to be used in a Australian paediatric health care setting, with findings suggesting that food insecurity is prevalent among families of children attending paediatric outpatient hospital appointments. While McKay and colleagues [14] have demonstrated that a brief tool measuring food insecurity could be used in a clinical setting as a component of a referral pathway for pregnant women who are identified as food insecure.…”
Section: Institutional Level Solutionsmentioning
confidence: 99%
“…In children, HFI has been associated with compromised mental health [ 16 ], as well as developmental, cognitive and behavioural (internalising and externalising) anomalies [ 17 ]. In parts of Australia, from one in four to one in two households experience food insecurity on a regular basis [ 7 , 18 , 19 , 20 , 21 , 22 ]. The primary determinant of HFI is low income combined with the high cost of living, including unaffordable housing, utilities, healthcare, education, and food [ 3 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%